SELF CLEANING OF EARS BY VARIOUS OBJECTS CAUSES MULTIPLE DISEASES OF EXTERNAL EAR - Bukhari, Syed Muhammad Asad Shabbir; Aslam, Sohail; Afzal, Mahrukh; Riaz, Naeem; Abbas, Asim; Afridi, Jehangir Ahmed; Khan, Muhammad Fahad Wasim (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the association of multiple diseases of external ear with the use of various objects and cotton buds. Study Design: Case control study. Place and Duration of Study: Ear Nose Throat Department, Pakistan Naval Ship Shifa Karachi, from Jan to Oct 2020. Methodology: All the patients having multiple diseases of external ear were included as cases. Controls were selected from the healthy volunteers from general populations. Results: Total number of subjects in this study was 140 with the mean age 25.11 ± 11.21 years (2-55 years of age range). Out of them, 82 were male and 58 were female. Odds ratio was 16.07. Conclusion: There is a solid relationship of illnesses of external ear with the utilization of cotton buds. This detrimental practice should be incapacitated by featuring the notice by brands owners of cotton bud and safety instructions at different instructive levels.